Role of nutrition in providing pro-/anti-inflammatory balance emerging research and opportunities - Gunsen, Ugur 1965-; Atan, Ramazan Mert 1995- (Advances in medical diagnosis, treatment, and care (AMDTC) book series, 2020)
"This book explores the role of nutrition in providing pro-/anti-inflammatory balance. It also examines the formation process of inflammation, biomarkers used for diagnosis, and diseases affected by inflammation"--